Design and Prototyping of a Mechatronic System as a Drag Reduction Device for Busses - Kavadar, Gökhan; Keçeci, Emin Faruk; Keçeci, Emin Faruk (Izmir Institute of Technology, 2006)
In this thesis study it is intended to design a mechatronic device which will act as a drag reducer for busses. The drag reduction device will be a self operating system, which will be attached onto the front side of the bus. Since the device will operate at the front of the vehicle, it will reduce the front drag force. The mechatronic drag reduction device will have two states; these are the open and close states. Therefore, the device will operate only when it is necessary to operate. That is, normally when the drag force experienced by the vehicle is not at important levels, then the device will stay closed. In the closed position the device will occupy the least space so that it does not cause any difficulties for the driver. However, when the drag force increases, then the device opens and builds itself on the front of the vehicle. The basic idea behind this device is to produce an extra volume of mass at the front of the bus, which will change the incoming airflow, so that the least resistance is experienced by the bus. By reducing the drag force a corresponding amount of fuel saving could be achieved. The mechatronic device design is made by parametric solid modeling software SolidWorks. The shape of the mechatronic device and the mechanism design will all be made in computer environment. The fluid flow analyses will be also made by using an Engineering fluid dynamics software program called Cosmos FloWorks. The most efficient shape for the mechatronic drag reduction device will be designed by the computer software. In the scope of this project a small low-speed wind tunnel will be constructed. Besides the virtual analyses made with computer software, real flow tests will be carried out by using a 1:50 scale model bus, attached with a model of the mechatronic drag reduction device. In the wind tunnel tests, the relative reduction in drag forces will be investigated.
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2006
Includes bibliographical references (leaves: 90-91)
Text in English; Abstract: Turkish and English
xii, 97 leaves
Keywords: TL574.D7 .K21 2006; Drag (Aerodynamics); Mechatronics; Bus industry